Evaluation of grass quality in grazing and ungrazing paddocks in a buffalo's breeding and research centre, Telupid, Sabah - Siti Hafizah Mohd Salleh
Buffalo production is dependent almost entirely on forages. Thus, adequate nutrition role in the productivity ofbuffaloes. In Buffalo Breeding and Research Centre, Telupid, Sabah, the grasses that are fed to buffalo are Signal Grass (Brachiaria decumbens). The growth of the buffalo depends on the nutritional quality of grass that is provided to them. Therefore, the particular grass was be evaluated to know the status and quality of the nutrient contents which are related to growth performance of the buffalo. This study was conducted to evaluate the nutrient contents of signal grass since there is no study on evaluation of grass quality in this farm. In addition, the comparison was made in nutrient contents of signal grass between the graze and ungrazed areas. A total of 12 grass samples were taken of which 6 samples each from grazed area and ungrazed area. The grass samples were taken by using the quadrat and all the samples were air dried and sent to UPM for proximate analysis. Two analyses were done which were DM and CP. The values of Van Soest Fibre were also determined such as NDF, ADF and ADL. The statistical analysis was performed using the SPSS (version 16.0) statistical software. It was assessed using Independent Sample T-test and correlation analysis. A p<0.05 was considered to be significant. The results revealed that there were significant different between ungrazed and grazed area for DM and CP. There was also significant negative correlation between DM and CP content of signal grass. In conclusion, grass in grazed area has better nutritive value compare to grass in ungrazed area. In addition, the relationship between DM and CP was an inversely related where when DM increase, the CP decrease. Thus, the results of the current study could be used to improve the performance of farm and as a reference for future study.